2011
DOI: 10.5194/angeo-29-283-2011
|View full text |Cite
|
Sign up to set email alerts
|

Resolving issues concerning Eskdalemuir geomagnetic hourly values

Abstract: Abstract.The hourly values of the geomagnetic field from 1911 to 1931 derived from measurements made at Eskdalemuir observatory in the UK, and available online from the World Data Centre for Geomagnetism at http://www.wdc. bgs.ac.uk/, have now been corrected. Previously they were 2-point averaged and transformed from the original north, east and vertical down values in the tables in the observatory yearbooks. This paper documents the course of events from discovering the post-processing done to the data to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…We conclude that there is no problem with the Potsdam data. Bearing in mind the Eskdalemuir data change discussed earlier Macmillan and Clarke, 2011) we believe the most likely explanation is that the diurnal variation in the EKT data at this time may have been smoothed or may even have been recorded less often than hourly and interpolated: either would have artificially raised the r UT values.…”
Section: Comparing and Combining Indicesmentioning
confidence: 99%
“…We conclude that there is no problem with the Potsdam data. Bearing in mind the Eskdalemuir data change discussed earlier Macmillan and Clarke, 2011) we believe the most likely explanation is that the diurnal variation in the EKT data at this time may have been smoothed or may even have been recorded less often than hourly and interpolated: either would have artificially raised the r UT values.…”
Section: Comparing and Combining Indicesmentioning
confidence: 99%
“…The fit to the Master Composite is nearly as close as for the full 24-hour coverage, because the two hours chosen are near the average times of maximum effect. There is small systematic discrepancy for ESK before 1932 due to a change of data reduction in 1932 (MacMillan and Clarke, 2011). Because such meta-information is rarely available, we generally make no attempt to correct for known and unknown minor changes.…”
Section: Normalization Of the Diurnal Range Rymentioning
confidence: 99%
“…For example, in developing the IHV index (Svalgaard et al, 2004;Svalgaard and Cliver, 2007) using data from many stations, Leif Svalgaard in 2004 noted in a letter to the data curators that there appeared to be an error in the early hourly mean data from the Eskdalemuir station, something also noted by Martini and Mursula (2006). From careful comparisons with data from nearby stations, this error was corrected by Macmillan and Clarke (2011). Another example was poor calibration of the horizontal force variometer at Helsinki for a 6-year interval noted by Svalgaard (2014), which was causing the horizontal H component to be too small; Lockwood et al (2014a) also found that correcting for this using data on the vertical Z component indeed brought the data in line with the observations from other stations, particularly at the nearby St. Petersburg station.…”
Section: Calibration and Checking Of Geomagnetic Datamentioning
confidence: 99%